Pengaruh Kualitas Produk, Harga Dan Store Atmosphere Terhadap Keputusan Pembelian Produk Eiger - M. Sofyan Hadi; M Aksal Asmawi; Eman Sulaeman (Jurnal Ilmiah Wahana Pendidikan, 2023)
There is a lot of competition in the business world that requires every entrepreneur to be able to compete in the business world, especially in an Outdoor Store, and there are several complaints from some customers about the high price of Eiger products, the quality of Eiger products, inconvenience in the Eiger Store, not appropriate. This type of research is research using a quantitative approach. The analytical model used is multiple linear regression analysis. The sample in this study were visitors and buyers of Eiger products, totaling 100 people. The type of data in this study is primary data obtained by using the questionnaire method. The sample selection method is purposive sampling method using the Slovin formula, and data processing using SPSS software. The results contained in this study are Price, Quality, Store Atmosphere, simultaneously have a significant effect on purchasing decisions for Eiger products by 0.000 or 0.10. Another result is that the Quality Variable has a positive and significant effect on purchasing decisions at the Eiger Store which has a value of 0.007 0.10, then the Price Variable has a positive and significant effect on purchasing decisions at the Eiger Store which has a value of 0.008 0.10 and the Store Atmosphere variable partially has a positive and significant effect on purchasing decisions at the Eiger Store which has a value of 0.016 0.10. It is concluded that all of these factors have a significant effect on purchasing decisions at the Eiger Store.